2021
DOI: 10.1101/2021.02.24.432751
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extracellular S100B alters spontaneous Ca2+fluxes in dopaminergic neurons via L-type voltage gated calcium channels: Implications for Parkinson’s disease

Abstract: Parkinson's disease (PD) is associated with an abnormal increase in S100B within the midbrain and cerebrospinal fluid. In addition, overexpression of S100B in mice accelerates the loss of substantia nigra pars compacta (SNc) dopaminergic (DA) neurons, suggesting a role for this protein in PD pathogenesis. We found that in the mouse SNc, S100B labeled astrocytic processes completely envelop the somata of tyrosine hydroxylase (TH) positive DA neurons. Based on this finding, we rationalized that abnormal increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…This suggests that the mechanism of voltage sensing is dependent on SMS, while the influx of ions through VGCCs is regulated by mechanisms that do not depend on SMS. Additionally, in our recent work, we have proved that the activity of L-type VGCC in DA neurons did not depend on the calcium release from the endoplasmic reticulum. We have also shown that the activity of L-type VGCC mainly depends on the extracellular Ca 2+ level rather than the intracellular Ca 2+ store.…”
Section: Resultsmentioning
confidence: 75%
“…This suggests that the mechanism of voltage sensing is dependent on SMS, while the influx of ions through VGCCs is regulated by mechanisms that do not depend on SMS. Additionally, in our recent work, we have proved that the activity of L-type VGCC in DA neurons did not depend on the calcium release from the endoplasmic reticulum. We have also shown that the activity of L-type VGCC mainly depends on the extracellular Ca 2+ level rather than the intracellular Ca 2+ store.…”
Section: Resultsmentioning
confidence: 75%